METHODOLOGY OF TEACHING NATURAL NUMBERS AND SIMPLE FRACTIONS WITH VOWELS (Spectrum Journal of Innovation, Reforms and Development, 2024)
Completion of basic arithmetic operations. In this, every student should know how to divide natural numbers (in millions) into unit units, subtraction tasks, multiplication and division of natural numbers (including division of remainders in simple numbers), and the solutions of multiplication by one and the other, as well as these operations. It is necessary for the teacher to take into account the opinions of the main features of the quick execution of actions, the ability to acquire skills and competences.